Penyusunan Kamus Elektrik Leksikon Jenis Tuturan “Rasa Sakit” Dalam Konteks Etnolinguistik Dialek Banyumasan Sebagai Bahan Pembelajaran Etnofarmakologi - Wilda Putri Festiyanti; Indira Pipit Miranti (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2021)
"The preparation of an electric lexicon dictionary of the speech type 'pain' in the ethnolinguistic context of the Banyumasan dialect as EthnoPharmacological Learning material" is scheduled to be carried out in several stages of research, because it is not possible to do it in one complete study. The main objective of this first research in a series of studies that produced the final result in the form of an electric dictionary was to begin with collecting/recording lexicons of types of pain speech using a combined method of observation, interviews and documentation. The researcher goes directly into the community so that he can see and observe naturally how the lexicons of the speech type 'pain' are pronounced in society. The target of interviews and observations was the community in the Banyumas residency area which was limited to only Banyumas, Purbalingga and Cilacap as respondents for this first study. Using the full sampling data collection technique, 103 lexicons of the type of 'pain' speech were obtained according to the part of the body that feels the pain. Then, each of these lexicons is translated into Indonesian and there is a pain lexicon that cannot be translated directly into Indonesian. This proves that the Banyumasan Javanese dialect has a more detailed and complete lexicon/vocabulary than Indonesian and deserves to be preserved as one of the regional languages ​​with a large number of speakers on the island of Java